Geological carbon storage in northern Irish basalts: prospectivity and potential - Andrews, Graham D. M. (Frontiers in Climate, 2023)
Carbon mineralization and storage in basaltic rock sequences is a developing technology but faces challenges with uptake and increases in scale. Northern Ireland (UK) is a useful analog for many parts of the world where thick basalt sequences could be used to aid in reaching carbon reduction and removal targets. Here I reanalyze and reinterpret available lithological, geochemical, and geophysical data to assess carbon storage potential. The physical and geochemical properties of the basalts are indistinguishable from those used for successful carbon sequestration in Iceland and Washington State (USA). Based on the thickness, composition, and potential permeability, I propose that this is a viable location for a series of small-volume stores (total volume ~9-12 MTCO2) suitable for capture at industrial point-sources or purpose-built CO2 'harvesting' facilities.The case for exploiting the CO2 storage potential in Northern Ireland is strengthened by (1) an increasingly urgent need to find socially and economically just decarbonization pathways needed to meet NI's targets, (2) increasing realization among policy experts that point-source CO2 capture and industrial decarbonization will be insufficient to meet those goals, due in part, to the size of the agricultural sector, and (3) the coincidence with plentiful renewable energy and geothermally-sourced industrial heat. These serendipitous relationships could be leveraged to develop CO2-'farms' where direct air capture operations are supplied by renewable energy (biomass and geothermal) and on-site geological storage. I envisage that these sites could be supplemented by CO2 from locally produced biomass as farmers are encouraged to transition away from raising livestock. Because CO2 can be captured directly from the atmosphere or via suitable biomass anywhere, NI's small size and position on the periphery of the UK and Europe need not be a disadvantage. Instead, NI's access to geological storage, renewable energy, and agricultural land may be a boon, and provide new opportunities to become a leader in carbon removal in basalt-covered regions worldwide, including India, East Africa, and many volcanic islands.